Investment climate assessment standards’ impact on the gross regional product growth of the Russian Federation subjects - L. I. Sergeyev; A. V. Samsonov (Вестник университета)
The study purpose is to identify the relationship between the provisions’ implementation of the regional investment standard and the growth of the gross regional product (GRP) in the Russian Federation subjects.   The average values’ statistically significant deviation of the GRP dynamics in 11 pilot regions of the Russian Federation and other subjects of the Russian Federation as an introduction result of regional investment standards developed by the Agency for Strategic Initiatives for the Promotion of New Projects (ANO “ASI”) together with the Ministry of Economic Development of the Russian Federation has been summarized. It is established that there is a statistically significant difference in the dynamics of the average GRP of the pilot and other regions of the Russian Federation, due to the implementing process of the provisions of the ANO “ASI” Standard. The provisions’ introduction of the ANO “ASI” Standard since 2012 has caused a statistically significant difference in the dynamics of the average GRP of the pilot and other regions of the Russian Federation. In fact, a significant outstripping dynamic of macroeconomic indicators for the development of pilot regions has not been achieved. The revealed situation testifies to the uneven movement of financial flows in the Russian Federation: about 45.8%of the profit of organizations falls on Moscow and St. Petersburg (2021). Despite the lack of outstripping dynamics of GRP and investments in fixed assets in comparison with the average value in the Russian Federation, the pilot regions managed to ensure a more stable dynamics of GRP in 2020. Despite the presence of partially lagging macroeconomic indicators’ dynamics of the pilot Russian Federation regions in comparison with the average values for the Russian Federation, the introduction of regional investment standards is an important condition for effective interaction between territorial authorities and a wide range of investors.